EVALUATING SAUDI EFL SECONDARY SCHOOLS STUDENTS' PERFORMANCE ON PAUL NATION'S STANDARDIZED VOCABULARY LEVEL TESTS - Alhaj, Ali Albashir Mohammed; Alwadai, Mesfer Ahmed Mesfer; Albuhairi, Mohammed Hamed (LLT Journal: A Journal on Language and Language Teaching, 2019)
The current study aims to evaluate Saudi EFL Secondary School students' performance on Paul Nation's Standardized vocabulary level tests. It also aims to examine the vocabulary size of EFL Saudi Secondary School students at Asir district. Two tools were used for collecting data. The first one was Paul Nation's Vocabulary Levels Test (VLT). The second tool was a questionnaire (TVLSQ) with 13 items. The purposive sample consisted of (80) students besides (20) English teachers. The study sample was selected from Abha secondary schools schools/Saudi Arabia. The study came out with the following results: Saudi EFL Secondary school students' vocabulary size word test falls within 1,000 frequency level, indicating that students are unable to gasp an average text. Saudi EFL Secondary School student who obtained higher marks in 1,000 word level also obtained higher marks in 2,000 word level and vice versa. These results confirmed the high correlation between the two tests which hits 0.76. Moreover, in Paul Nation's Vocabulary Levels Test (VLT) the more words Saudi EFL Secondary school student knows, the better score his/her four skills. To most secondary school teachers as well as students, English grammar is the main focus on their teaching and learning, not the vocabulary.